A Novel “Microbial Bait” Technique for Capturing Fe(III)-Reducing Bacteria - Macaulay, Babajide Milton; Boothman, Christopher; van Dongen, Bart E.; Lloyd, Jonathan Richard (Frontiers in Microbiology, 2020)
Microbial reduction of Fe(III) is a key geochemical process in anoxic environments, controlling the degradation of organics and the mobility of metals and radionuclides. To further understand these processes, it is vital to develop a reliable means of capturing Fe(III)-reducing microorganisms from the field for analysis and lab-based investigations. In this study, a novel method of capturing Fe(III)-reducing bacteria using Fe(III)-coated pumice “microbe-baits” was demonstrated. The methodology involved the coating of pumice (approx. diameter 4 to 6 mm) with a bioavailable Fe(III) mineral (akaganeite), and was verified by deployment into a freshwater spring for 2 months. On retrieval, the coated pumice baits were incubated in a series of lab-based microcosms, amended with and without electron donors (lactate and acetate), and incubated at 20℃ for 8 weeks. 16S rRNA gene analysis using the Illumina MiSeq platform showed that the Fe(III)-coated pumice baits, when incubated in the presence of lactate and acetate, enriched for Deltaproteobacteria (relative abundance of 52% of the sequences detected corresponded to Geobacter species and 24% to Desulfovibrio species). In the absence of added electron donors, Betaproteobacteria were the most abundant class detected, most heavily represented by a close relative to Rhodoferax ferrireducens (15% of species detected), that most likely used organic matter sequestered from the spring waters to support Fe(III) reduction. In addition, TEM-EDS analysis of the Fe(III)-coated pumice slurries amended with electron donors revealed that a biogenic Fe(II) mineral, magnetite, was formed at the end of the incubation period. These results demonstrate that Fe(III)-coated pumice “microbe baits” can potentially help target metal-reducing bacteria for culture-dependent studies, to further our understanding of the nano-scale microbe-mineral interactions in aquifers. Potential applications for in-situ enrichment techniques are discussed.